Anatomy and Dynamics of Oppression - Hilliard, Asa G., III. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
Education has traditionally been a tool of colonialists, who used it to destroy peoples' cultural histories and to create new cultural myths (such as race) designed to divide, demean, and debilitate the colonized group. Many concepts passed on through the educational system and through language have contributed to a form of cultural mental illness in which the objective realities of history and biology are distorted by the colonists' biases. Human relations educators must select strategies based on the theory of oppression to direct their work towards causes, not symptoms. In order to provide quality education, they should not feel bound to ethnically prejudicial testing, but should concentrate on: (1) teaching the truth (not the myth); (2) stressing historical continuity; (3) fostering self-determination and self-knowledge; and (4) instilling the spirit of liberation, which is the knowledge and capacity to choose and create. (Author/WI)
ERIC Note: Address delivered at the National Conference on Human Relations in Education (1st, Minneapolis, Minnesota, June 20, 1978).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Black History; Colonialism; Educational Discrimination; Educational Quality; Human Relations; Quality of Life; Racial Discrimination; Racism; Reports, Research